On nonlocal symmetries of a system of chemotaxis equations with derivative nonlinearity - Serov, M. I.; Podoshvelev, Yu. G. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.912With the help of nonlocal equivalence transformations, the system of chemotaxis equations is associated with a system of convection-diffusion equations. The Lie symmetry of the obtained system is used to construct nonlocal ansatzes and to reduce and find exact solutions of the system of chemotaxis equations.